2014
DOI: 10.1093/mnras/stu2458
|View full text |Cite
|
Sign up to set email alerts
|

Doppler images of the eclipsing binary ER Vulpeculae

Abstract: We present Doppler images of both components of the eclipsing binary system ER Vul, based on the spectra obtained in November, 2006 September and 2008 November. The least-squares deconvolution technique is used for enhancing the signal-to-noise ratios of the observed profiles. The new surface images reveal that both stars of ER Vul show strong starspot activities and the starspots appear at various latitudes. The surface maps of 2006 and 2008 both show the presence of large high-latitude starspots on each com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…We conclude that there is significant spot coverage on the inner hemisphere (white dwarf facing side of the M star) observed on all maps. This spot distribution -where there is a higher density of spots on the hemisphere facing the companion star -is similar to that observed in many other systems, such as the pre-CV V471 Tau (Hussain et al 2006), the eclipsing binary ER Vul (Xiang et al 2015), and the close binary σ 2 CrB (Strassmeier & Rice 2003). Furthermore, Kriskovics et al (2013) suggested that the hot-spots mapped on the companion-facing hemisphere in V824 Ara may indicate the strong interaction between the magnetic fields of the component stars, as is commonly observed in close RS CVn-type binaries.…”
Section: Surface Mapssupporting
confidence: 84%
“…We conclude that there is significant spot coverage on the inner hemisphere (white dwarf facing side of the M star) observed on all maps. This spot distribution -where there is a higher density of spots on the hemisphere facing the companion star -is similar to that observed in many other systems, such as the pre-CV V471 Tau (Hussain et al 2006), the eclipsing binary ER Vul (Xiang et al 2015), and the close binary σ 2 CrB (Strassmeier & Rice 2003). Furthermore, Kriskovics et al (2013) suggested that the hot-spots mapped on the companion-facing hemisphere in V824 Ara may indicate the strong interaction between the magnetic fields of the component stars, as is commonly observed in close RS CVn-type binaries.…”
Section: Surface Mapssupporting
confidence: 84%
“…In order to investigate the starspot activities on active close binaries, we have carried out a series of highresolution spectroscopic observations on targets with various stellar parameters and evolutionary stages (Gu et al 2003;Xiang et al 2014Xiang et al , 2015. In this work, we have derived the surface images of the K subgiant component of SZ Psc for 2004 November, 2006 September, October, November and December, through Doppler imaging technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several active single rapid rotators, such as AB Dor (Collier Cameron & Unruh 1994) and FK Com-type stars (Strassmeier et al 1999), were also reported to have large polar active regions. In our previous works, we found persistent highlatitude or polar features on the active binaries with various rotational speeds, such as II Peg (v sin i = 22 km s −1 ; Xiang et al 2014), SZ Psc (v sin i = 67.7 km s −1 ; Xiang et al 2016) and ER Vul (v sin i = 80 km s −1 ; Xiang et al 2015).…”
Section: Discussionmentioning
confidence: 83%
“…The Doppler imaging technique can offer a better constraint on spot latitudes. In order to investigate the spot activities of active binary stars, we continued to monitor a set of RS CVn-type binary systems (Gu et al 2003;Xiang et al 2014Xiang et al , 2015Xiang et al , 2016. In this study, we performed high-resolution spectroscopic observations on the active binary prototype RS CVn using three telescopes located at different observing sites.…”
Section: Introductionmentioning
confidence: 99%